Deconstruction and transformation of gender stereotypes through the role of clerics in the practice of propagation in Aceh: A socio-religious study - Jasafat, Jasafat; Likin, Soijah; Balqis, Syamira (UIN Ar-Raniry Banda Aceh, 2025)
Ulama in Aceh face significant challenges in integrating gender perspectives into their da'wah practices. The dominance of patriarchal culture and limited gender literacy often leads to the reinforcement rather than the deconstruction of gender stereotypes. This study employs a socio-religious approach to examine how ulama, as central figures in society, simultaneously sustain and contest social constructions that restrict gender roles—using qualitative methods including in-depth interviews, participant observation, and analysis of da'wah documents. The study finds that da'wah narratives frequently reproduce socially and religiously legitimized gender stereotypes. Nevertheless, some ulama have initiated efforts to challenge these norms by offering more inclusive and gender-just interpretations, aligning with the spirit of rahmatan lil 'alamin. The findings suggest ulama's role extends beyond preserving traditional values to acting as agents of change who can facilitate social transformation through gender-responsive da'wah. Achieving such a transformation requires synergy between ulama, communities, and progressive socio-religious policies to balance religious principles with social justice. This study underscores the importance of continuous dialogue and collaboration among ulama, educational institutions, and women's rights advocates to promote inclusivity within religious contexts. By integrating gender-sensitive approaches into religious discourse and curricula, sustainable progress toward equality can be fostered. Ultimately, the research emphasises that ulama's engagement in these efforts is vital for building a more inclusive, equitable society in Aceh and potentially beyond.